An investigation of the spatial distribution of dengue cases in Johor Bahru, Johor, Malaysia - Hamidun, Shahril; Che Dom, Nazri; Salleh, Siti Aekbal; Abdullah, Samsuri; Precha, Nopadol; Dapari, Rahmat (Taylor and Francis, 2022)
In recent decades, dengue fever has spread throughout developing countries, including Malaysia. Understanding the distribution pattern is thus important for the sustainability of urbanization. The goal of this study is to examine the trend of dengue cases reported in Johor Bahru District from 2015 to 2019, as well as the spatial pattern of dengue transmission in relation to weather parameters. The distribution pattern and spatial mean centre for dengue cases were found to be localized in the centre of Johor Bahru region, according to spatial statistical analysis. The extended polygon of dengue cluster spanned from the east to the west of Johor Bahru district, according to directional distribution. The least standard distance for dengue cases was 0.104 m in 2015, and the greatest was 0.120 m in 2018, whereas dengue cases in 2016, 2017, and 2019 were measured at 0.111 m and 0.116 m, 0.106 m respectively. Dengue cases in Johor Bahru district were likewise concentrated, according to the average nearest neighbour analysis. Temperature (r = 0.222) was found to be positively connected with dengue cases, although rainfall (r = −0.124) and relative humidity (r = −0.152) were in contrast with dengue cases throughout the five years of study period. The outcomes of the these spatial statistical analyses revealed that dengue cases concentrated in the east to west of the research region from 2015 to 2019. Temperature is determined to be a substantial positive factor correlated for most study years.